2008
DOI: 10.1017/s1479262108923789
|View full text |Cite
|
Sign up to set email alerts
|

Genetic erosion and changes in distribution of sorghum (Sorghum bicolor L. (Moench)) landraces in north-eastern Ethiopia

Abstract: Ethiopia is believed to be the centre of origin and domestication for sorghum, where sorghum remains one of the main staple crops. Loss of biodiversity is occurring at an alarming rate in Ethiopia and crops, including sorghum, have long been recognized as vulnerable to genetic erosion. A major collection of sorghum germplasm was made in 1973 by Gebrekidan and Ejeta from north-eastern Ethiopia. A new collection of landraces was made in 2003, and these were field evaluated at Sirinka in 2004 along with represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…Consequently, landraces with 50% or more grain covered with glume were not important among the landraces evaluated. This result is in line with previous observation in farmers' fields (Shewayrga et al, 2008). Such landraces were not widely grown and most of them were small seeded (1000-seeds weight) with brown color and often with very loose or open panicle.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consequently, landraces with 50% or more grain covered with glume were not important among the landraces evaluated. This result is in line with previous observation in farmers' fields (Shewayrga et al, 2008). Such landraces were not widely grown and most of them were small seeded (1000-seeds weight) with brown color and often with very loose or open panicle.…”
Section: Discussionsupporting
confidence: 92%
“…The analyses for quantitative traits revealed wide variability among the landraces. Previous studies (Teshome et al, 1999;Seboka and van Hintum, 2006;Shewayrga et al, 2008) reported that farmers purposely maintain and grow many landraces to address various needs as well as risk aversion strategy, and the landraces vary in maturity, yield potential, stress tolerance, end-use quality and other agronomic traits. Diversity studies in NE Ethiopia have also shown high diversity for other crop landraces including tef (Assefa et al, 2001;Kefyalew et al, 2000), barley (Abebe et al, 2010;Mekonnon et al, 2015) and durum wheat (Eticha et al, 2005;Mengistu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low to moderate geographic differentiation could be attributed to frequent gene flow among fields as a consequence of seed exchanges among farmers, and/or to restriction of the intensity of genetic drift due to a high effective population size (Dje et al, 1999). Earlier observations (Shewayrga et al, 2008) showed that many landraces with the same local name are grown in two or more zones attributed to the existing farmers' seed system. Seeds are shared through gift, exchange in kind, and purchase.…”
Section: Genetic Structure and Differentiation Of Landracesmentioning
confidence: 99%
“…The majority of sorghum production in the country in general and NE Ethiopia in particular depends on landraces (Gebrekidan, 1973;Worede, 1992;Teshome et al, 1997Teshome et al, , 1999Seboka and van Hintum, 2006;Shewayrga et al, 2008). The sorghum grain is mainly used for Injera, a fermented flat bread and staple Ethiopian dish.…”
Section: Introductionmentioning
confidence: 99%